KEMATIAN MENURUT PARA FILOSOF - Syafi'in Mansur (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
As a human being, all people will meet the end of their life in this world. Hence, all philosophers agree that the death is a dead certainty from the God for all human beings . even th ough the death is painful and tearful for those who are left , the death must meet every boDy anytime.Death is a certainty for humans determined by God, they must be ready to receive it because all humans must experience it. Even though the death is mysterious and nobody knows when it comes and how he will die; however, the most important thing that everybocfy will be awaken inside the grave by God and he will be asked about their deeds during his life in the world. Whoever does many good deeds, he will be entered into the heaven; conversely, whoever does many bad actions, he will be entered into the hell.Key Words: Death, Greece philosophers, Muslim Philosophers, West Philosophers.